Kecemasan Informasi pada Mahasiswa Angkatan 2021 Program Studi Perpustakaan dan Ilmu Informasi UIN Malang - Yolanda, Rani (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2024)
This study aimed to describe information anxiety among students enrolled in the Library and Information Science Study Program at Maulana Malik Ibrahim State Islamic University, Malang, class of 2021. Information anxiety, as part of information behavior, concerns the feelings experienced by a person when confronted with information. This study used a descriptive quantitative method. A sample of 30 respondents from the 2021 class of students was selected. Data processing was based on the results of questionnaires. Information anxiety experienced by students enrolled in the Library and Information Science Study Program at UIN Malang class of 2021 showed diverse results, encompassing various barriers, including barriers with information sources, barriers with computers and the internet, barriers with libraries, barriers in finding information, barriers with technical aspects, and barriers with identifying information. Keywords: information anxiety, student information seeking, information behavior